Gesture and Sign: Cataclysmic Break or Dynamic Relations? - Müller, Cornelia (Frontiers in Psychology, 2018)
Abstract The goal of the article is to offer a framework against which relations between gesture and sign can be systematically explored beyond the current literature. It does so by a) reconstructing the history of the discussion in the field of gesture studies, focusing on three leading positions (Kendon, McNeill, Goldin-Meadow); and b) by formulating a position to illustrate how this can be achieved. The paper concludes by emphasizing the need for systematic cross-linguistic research on multimodal use of language in its signed and spoken forms.